The effect of adrenaline on desflurane-induced prolonged QTc interval: a randomized double-blind trial - Bestas, A.; Hanbeyoglu, O.; Keles, E.; Bayar, M. K. (Verduci Publisher, 2013)
BACKGROUND AND AIM: We investigated the effect of adrenaline on desflurane-induced prolonged corrected QT (QTc) interval. PATIENTS AND METHODS: Sixty-two adult patients scheduled for nasal surgery were included. Following intubation, packs soaked in physiological saline were used for Group C (control) and packs soaked in adrenaline (1/200,000, 5 ml) were used for Groups A1 and A2. Group A2 was given desflurane simultaneously with nasal packing; other groups were given desflurane following removal of the packs. QTc interval was evaluated at 9 periods, from prior to induction of anaesthesia to postoperative first hour. RESULTS: QTc interval was significantly reduced in Groups A1 and A2 compared to Group C during packaging (p < 0.001, p < 0.05 respectively), while QTc interval gradually prolonged after desflurane administration (p < 0.05 in Groups C compared to Groups A1 and A2). Patients did not develop arrhythmia. CONCLUSIONS: Our findings show that desflurane caused progressive prolongation of the QTc interval, and adrenaline shortened QTc interval only at application period of packs.
Keywords: Desflurane; Adrenaline; QTc interval